Moderasi Kualitas Auditor terhadap Pengaruh Leverage, Kepemilikan Manajerial, dan Kepemilikan Institusional Pada Manajemen Laba - L. Mamu, Yohanes Teofilus; Eka Damayanthi, I.Gusti Ayu (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
This study aims to determine the moderation of auditor quality to the effect of leverage, managerial ownership, and institutional ownership on earnings management. The research was conducted at a manufacturing company in Indonesia Stock Exchange 2012-2016. The sample of research is 71 companies. The analysis shows that leverage has a positive effect on earnings management, institutional ownership has a negative effect on earnings management, while managerial ownership has no effect on earnings management. The quality of the auditor weakens the effect of leverage on earnings management, the quality of the auditor reinforces the influence of institutional ownership on earnings management, while the quality of the auditor does not moderate the effect of managerial ownership on earnings management. Future research is expected to group managerial percentages above 5 percent thus increasing the significance of the effect of managerial ownership on earnings management.  Keywords : leverage, managerial ownership, institutional ownership, auditor quality, earnings management